EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) DAN GROUP INVESTIGATION (GI) PADA MATERI SEGIEMPAT DITINJAU DARI KECERDASAN MATEMATIS LOGIS SISWA - Susandi, Ardi Dwi; Budiyono, Budiyono; Sari S, Dewi Retno (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2014)
Abstyact:The objective of this research was to investigate the effect of the learning models on the learning achievement in Mathematics viewed from the mathematical logical quotient of the students. The learning models compared were the cooperative learning model of the TSTS type, the Cooperative Learning Model of the GI type, and the direct learning model. This research used the quasi experimental research. Its population was all of the students in Grade VII of State Junior Secondary Schools of Cirebon regency in Academic Year 2013/2014. The samples of the research were taken by using the stratified cluster random sampling technique and consisted of 364 students. They were grouped into three classes, namely: 123 in Experimental Class 1, 117 in Experimental Class 2, and 124 in Control Class. The instruments to gather the data were test of achievement in Mathematics on the learning material of Quadrangle, and test of mathematical logical quotient. The proposed hypotheses of the research were analyzed by using the two way analysis of variance with unbalanced cells. The results of the research were as follows. 1) The cooperative learning model of the TSTS type results in a better learning achievement in Mathematics than the cooperative learning model of the GI type and the direct learning model, the cooperative learning model of the GI type results in a better learning achievement in Mathematics than the direct learning model. 2) The students with the high mathematical logical quotient have a better learning achievement in Mathematics than those with the moderate mathematical logical quotient and those with the low mathematical logical quotient, the students with the moderate mathematical logical quotient have a better learning achievement in Mathematics than those with the low mathematical logical quotient. 3) There was an interaction the aforementioned learning models and the categories of the mathematical logical quotient on the learning achievement in Mathematics of the students.Keywords:TSTS, GI, and mathematical logical quotient.